1998
DOI: 10.1590/s1516-31801998000100007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe actinic rectitis

Abstract: The surgical technique utilized was considered to be adequate for the cases reported and is the first option for the maintenance of transit in patients with severe actinic rectitis since the anastomosis is performed using non-irradiated colon with the pectineal line, practically outside the pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have shown that alterations in genes that regulate basic cell functions such as cell-cell adhesion and ECM-cell adhesion are followed by penetration of the basal membrane, destroying the physical structure of the tissue [1]. Alterations in the expression of adhesion molecules can influence tumor aggression resulting in local infiltrative growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that alterations in genes that regulate basic cell functions such as cell-cell adhesion and ECM-cell adhesion are followed by penetration of the basal membrane, destroying the physical structure of the tissue [1]. Alterations in the expression of adhesion molecules can influence tumor aggression resulting in local infiltrative growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%